Intellectual Capital in Competitive Advantage through Green Human Resource Management - I Made Adi Suwandana; I Made Kartika; I Wayan Sugiartana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The wood craft industry in Badung Regency, Bali, significantly contributes to export value, yet faces challenges in maintaining sustainability and competitiveness. This study aims to examine the role of green human resource management as a mediator in the relationship between green human capital, green structural capital, green relational capital, and competitive advantage in wood small and medium enterprises. Employing a quantitative approach with descriptive and associative methods, the study sampled 267 enterprises from a population of 804 using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares. Findings reveal that green human capital, green structural capital, and green relational capital positively influence green human resource management and competitive advantage. Green human resource management significantly mediates these relationships, enhancing employees’ eco-friendly competencies, supporting efficient green systems, and fostering sustainable partnerships. These results underscore the critical integration of green human resource management and green intellectual capital to achieve sustainable competitive advantage in the wood small and medium enterprise sector. The study highlights the strategic importance of aligning human resource practices with environmental goals to enhance efficiency, innovation, and market reputation, ensuring long-term sustainability and competitiveness.